METHOD OF IDENTIFYING COMMON GLIKORPOTEINS IN SALIVA - Romanenko, E.G.; Klenina, I.A. (World of Medicine and Biology, 2012)
A method of identifying common glikorpoteins in saliva. The lowest level of glycoproteins reported in children with inflammatory and erosive changes in the mucosa of the gastroduodenal zone. Shown that the decrease in the number of glycoproteins in the saliva of children with gastroduodenal pathology leads to the deterioration of oral health with the subsequent development of inflammation in the mucosa of the gums.